Effects of metformin on the glycemic control, lipid profile, and arterial blood pressure of type 2 diabetic patients with metabolic syndrome already on insulin - Mourão-Júnior,C.A. (2006)
Fifty-seven type 2 diabetic patients with metabolic syndrome and on insulin were assessed by a paired analysis before and 6 months after addition of metformin as combination therapy to evaluate the impact of the association on glycemic control, blood pressure, and lipid profile. This was a historical cohort study in which the files of type 2 diabetic patients with metabolic syndrome on insulin were reviewed. The body mass index (BMI), waist circumference, lipid profile, A1C level, fasting blood glucose level, daily dose of NPH insulin, systolic blood pressure, and diastolic blood pressure were assessed in each patient before the start of metformin and 6 months after the initiation of combination therapy. Glycemic control significantly improved (P < 0.001) after the addition of metformin (1404.4 ± 565.5 mg/day), with 14% of the 57 patients reaching A1C levels up to 7%, and 53% reaching values up to 8%. There was a statistically significant reduction (P < 0.05) of total cholesterol (229.0 ± 29.5 to 214.2 ± 25.0 mg/dL), BMI (30.7 ± 5.4 to 29.0 ± 4.0 kg/m²), waist circumference (124.6 ± 11.7 to 117.3 ± 9.3 cm), and daily necessity of insulin. The reduction of total cholesterol occurred independently of the reductions of A1C (9.65 ± 1.03 to 8.18 ± 1.01%) and BMI and the reduction of BMI and WC did not interfere with the improvement of A1C. In conclusion, our study showed the efficacy of the administration of metformin and insulin simultaneously without negative effects. No changes were detected in HDL-cholesterol or blood pressure.